2017
DOI: 10.1177/1069072717727483
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Childhood Career Development Scale Among Italian Middle School Students

Abstract: During early adolescence, individuals engage in exploring educational opportunities, beginning to develop a career identity, contemplate future careers, and make tentative career decisions. Choices made during this period may have a strong effect on one's academic and career future, and in many countries young adolescents must make important and sometimes final academic and career choices that impact the rest of their lives. Despite this, research on early adolescence is severely lacking. To address this gap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The instrument development studies reported the Cronbach's alphas of 0.66 (Schultheiss & Stead, 2004) and 0.70 (Stead & Schultheiss, 2003) for this scale among elementary school students. The Cronbach's alpha was 0.74 in another study of middle school students (Ferrari et al, 2018). The internal consistency reliability of the current study was 0.75.…”
Section: Childhood Career Developmentmentioning
confidence: 45%
See 2 more Smart Citations
“…The instrument development studies reported the Cronbach's alphas of 0.66 (Schultheiss & Stead, 2004) and 0.70 (Stead & Schultheiss, 2003) for this scale among elementary school students. The Cronbach's alpha was 0.74 in another study of middle school students (Ferrari et al, 2018). The internal consistency reliability of the current study was 0.75.…”
Section: Childhood Career Developmentmentioning
confidence: 45%
“…Sample items included “I try to find out more about what I learn at school,” “I wonder about the things I learn in school,” and, “My family says that I am curious about things.” The instrument development studies reported the Cronbach's alphas of 0.66 (Schultheiss & Stead, 2004) and 0.70 (Stead & Schultheiss, 2003) for this scale among elementary school students. The Cronbach's alpha was 0.74 in another study of middle school students (Ferrari et al., 2018). The internal consistency reliability of the current study was 0.75.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on all these, in this study, career development is considered a concept that expresses how ready students are to make a career choice based on their plans, interests, self‐concepts, research and investigation activities, curiosity, role models, and how their current actions will affect their future. Early adolescence is very important as young people develop their career choices and make educational and career decisions in early adolescence (Ferrari et al., 2018). This process, knowing the factors that shape the career development of individuals and working on regulating these factors, can enable individuals to make a good start in their career journey.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ECI might be a particular concern in increasingly dynamic work‐life contexts (Hirschi & Koen, 2021; Spurk et al, 2016). Nowadays, young individuals have to navigate their educational and career paths in often unpredictable and fast‐changing environments characterized by occupational erosion due to rapid technological development and by difficulties in forecasting what sorts of vocational skills and competences will be needed in future working life (Ferrari et al, 2018; Gati & Kulscár, 2021; Hayden et al, 2021; Hirschi & Koen, 2021; Hoff et al, 2022; Khattab et al, 2022; Klug, 2020). Also, contemporary career theories, e.g., cognitive information processing theory (CIP; Osborn et al, 2013; Sampson et al, 2004), which focus on career decision‐making and insecurity in transition stages, underscores the external contextual factors underlying career decisions and actions.…”
Section: Introductionmentioning
confidence: 99%